Measurement of gastric meal and secretion volumes using magnetic resonance imaging. (16th January 2015) - Hoad, C L; Parker, H; Hudders, N; Costigan, C; Cox, E F; Perkins, A C; Blackshaw, P E; Marciani, L; Spiller, R C; Fox, M R; Gowland, P A
Abstract: MRI can assess multiple gastric functions without ionizing radiation. However, time consuming image acquisition and analysis of gastric volume data, plus confounding of gastric emptying measurements by gastric secretions mixed with the test meal have limited its use to research centres. This study presents an MRI acquisition protocol and analysis algorithm suitable for the clinical measurement of gastric volume and secretion volume. Reproducibility of gastric volume measurements was assessed using data from 10 healthy volunteers following a liquid test meal with rapid MRI acquisition within one breath-hold and semi-automated analysis. Dilution of the ingested meal with gastric secretion was estimated using a respiratory-triggered T1 mapping protocol. Accuracy of the secretion volume measurements was assessed using data from 24 healthy volunteers following a mixed (liquid/solid) test meal with MRI meal volumes compared to data acquired using gamma scintigraphy (GS) on the same subjects studied on a separate study day. The mean ± SD coefficient of variance between 3 observers for both total gastric contents (including meal, secretions and air) and just the gastric contents (meal and secretion only) was 3  ±  2% at large gastric volumes (>200 ml). Mean ± SD secretion volumes post meal ingestion were 64  ±  51 ml and 110  ±  40 ml at 15 and 75 min, respectively. Comparison with GS meal volumes, showed that MRI meal only volume (after correction for secretion volume) were similar to GS, with a linear regression gradient ± std err of 1.06  ±  0.10 and intercept −11  ±  24 ml. In conclusion, (i) rapid volume acquisition and respiratory triggered T 1 mapping removed the requirement to image during prolonged breath-holds (ii) semi-automatic analysis greatly reduced the time required to derive measurements and (iii) correction for secretion volumes provided accurate assessment of gastric meal volumes and emptying. Together these features provide the scientific basis of a protocol which would be suitable in clinical practice.